Analyzing Branch‐specific Dendritic Spikes Using an Ultrafast Laser Scalpel - Castañares, Michael L.; Bachor, Hans-A.; Daria, Vincent R. (Frontiers in Physics, 2020)
Dendritic spikes facilitate neuronal computation and they have been reported to occur in various regions of the dendritic tree of cortical neurons. Spikes that occur only on a select few branches are particularly difficult to analyze especially in complex and intertwined dendritic arborizations where highly localized application of pharmacological blocking agents is not feasible. Here, we present a technique based on highly targeted dendrotomy to tease out and study dendritic spikes that occur in oblique branches of cortical layer five pyramidal neurons. We first analyze the effect of cutting dendrites in silico and then confirmed in vitro using an ultrafast laser scalpel. A dendritic spike evoked in an oblique branch manifests at the soma as an increase in the afterdepolarization (ADP). The spikes are branch-specific since not all but only a few oblique dendrites are observed to evoke spikes. Both our model and experiments show that cutting certain oblique branches, where dendritic spikes are evoked, curtailed the increase in the ADP. On the other hand, cutting neighboring oblique branches that do not evoke spikes maintained the ADP. Our results show that highly targeted dendrotomy can facilitate causal analysis of how branch-specific dendritic spikes influence neuronal output.